Effect Of Dietary Supplementation Of Garlic (Allium Sativum) On Weight Gain And Cholesterol Level In Broilers - Singh, A.P.; Ramteke, B.N.; Meshram, A.Y. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A biological trial was conducted for a period of 6 weeks to study the effect of graded levels of Garlic (Allium sativum) supplementation on growth performance and muscle cholesterol including serum lipid profile in broilers. The body weight was significantly increased (P
Keywords: Broilers; Meat and Serum cholesterol; Garlic